2007
DOI: 10.1097/01.aog.0000261899.87638.0a
|View full text |Cite
|
Sign up to set email alerts
|

Low-Weight Polypropylene Mesh for Anterior Vaginal Wall Prolapse

Abstract: Anterior colporrhaphy, reinforced with, tailored mesh significantly reduced the rate of recurrence of anterior vaginal wall prolapse compared with the traditional operation, but was associated more often with stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
2
22

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(142 citation statements)
references
References 14 publications
7
111
2
22
Order By: Relevance
“…The appearance of prolapse in a well supported compartment is an issue which occurs after all surgery for prolapse whether conventional or using mesh [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of prolapse in a well supported compartment is an issue which occurs after all surgery for prolapse whether conventional or using mesh [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure rate of the mesh was 14%; also small, nonsymptomatic exposures were recorded. In the literature, mesh exposure rates have varied between 7% and 17% [10,[14][15][16]. The erosion rate of vaginal meshes may to be related to surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with apical fixation or concomitant apical surgery [71][72][73][74][75][76][77][78][79], anterior repair using a synthetic mesh (excluding Prolift ® and Perigee ® ) had a cumulative success rate of 93 %; the cumulative success rate of studies without apical fixation or without standard apical surgery [80][81][82][83][84][85][86][87][88][89] was 83 %. The cumulative rate of mesh erosion was 8 % (137/1740); the cumulative rate for chronic pain and de novo dyspareunia was 7% (59/846).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%
“…However, one study evaluated the long-term data after three years and no longer found any significant difference between the two procedures [72,120]. The CARE study [121] compared abdominal sacrocolpopexy in preoperatively continent women with (n = 157) and without (n = 165) concomitant Burch colposuspension.…”
Section: Continent Women With Genital Prolapsementioning
confidence: 99%